2022
DOI: 10.3390/ijerph19042120
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-Emission Characteristics and Influencing Factors in Growing and Shrinking Cities: Evidence from 280 Chinese Cities

Abstract: The CO2 emission-mitigation policies adopted in different Chinese cities are important for achieving national emission-mitigation targets. China faces enormous inequalities in terms of regional economic development and urbanization, with some cities growing rapidly, while others are shrinking. This study selects 280 cities in China and divides them into two groups of growing cities and two groups of shrinking cities. This is achieved using an index called “urban development degree,” which is calculated based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…The study recommends reducing the national income gap, stimulating household consumption, increasing infrastructure construction expenditures, investing in public health and education, mitigating environmental pollution to improve well-being and social welfare, and addressing inequality in sustainable economic welfare development. Additionally, addressing inequality remains a critical aspect of global development, particularly in low-income countries [64]. A study by Selseng, T., Linnerud, K., and Holden, E. (2022) emphasizes the significance of decreasing inequality to foster sustainable development [64].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study recommends reducing the national income gap, stimulating household consumption, increasing infrastructure construction expenditures, investing in public health and education, mitigating environmental pollution to improve well-being and social welfare, and addressing inequality in sustainable economic welfare development. Additionally, addressing inequality remains a critical aspect of global development, particularly in low-income countries [64]. A study by Selseng, T., Linnerud, K., and Holden, E. (2022) emphasizes the significance of decreasing inequality to foster sustainable development [64].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, addressing inequality remains a critical aspect of global development, particularly in low-income countries [64]. A study by Selseng, T., Linnerud, K., and Holden, E. (2022) emphasizes the significance of decreasing inequality to foster sustainable development [64]. Furthermore, a study by Jiang, S., Mentel, G., Shahzadi, I., Ben Jebli, M., and Iqbal, N. (2022) recommends that governments should prioritize reducing income inequality and promoting the use of renewable energy to achieve Sustainable Development Goals [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urban growth or shrinkage is a comprehensive concept that is based on population increase or decrease and reflects the development problems such as land use efficiency, public infrastructure, economic development, fiscal revenue, and social public service capacity [48,49]. Referring to Tong et al [35], this study focused on four dimensions-population, economy, space, and society-in order to build a multidimensional evaluation system for urban growth and shrinkage (Table 1). The three variables chosen to illustrate the population dimension are the natural population growth rate, the total population, and the population density.…”
Section: Classification Of Growing and Shrinking Citiesmentioning
confidence: 99%
“…Sun et al [33] reported that shrinking cities have lower eco-efficiency than growing cities, while Xiao et al [34] reported that CO 2 emissions continued to rise in rapidly shrinking cities, although they peaked in other cities in China during 2011-2013. Tong et al [35] indicated that the population and economy significantly promote carbon emissions, while in shrinking cities, technology and tertiary industries have significant negative effects on carbon emissions. Previous studies have shown that CO 2 emissions display differing patterns in growing and shrinking cities; however, urban forms have been neglected in most cases.…”
Section: Introductionmentioning
confidence: 99%